EDUKASI PENCEGAHAN DAN PENANGANAN AWAL CEDERA SPRAIN ANKLE PADA SISWA SMA DI KOTA BANJARMASIN - Ridhani, Akhmad; Hasanah, Uswatun; Ridhayanti, Rizky; Sadu, Bernadus; Wicaksono, Utomo; Prayogo, Dadan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Ankle sprains are one of the most common musculoskeletal injuries in active adolescents, especially high school students who regularly participate in sports activities. Lack of knowledge about early treatment and injury prevention strategies can increase the risk of complications and recurrence. This service activity aims to improve the knowledge and skills of high school students in Banjarmasin City in the initial handling and prevention of ankle sprain injuries through a participatory educational approach. The implementation method uses a combination of interactive lectures, demonstrations, and re-demonstrations with a pre-test–post-test group design. A total of 60 students were purposively selected as participants, and data were collected using multiple-choice questionnaire instruments to measure the level of knowledge before and after the activity. The analysis was carried out descriptively by comparing the frequency and percentage of correct answers in the pre-test and post-test. The results showed a substantial improvement in the level of knowledge, from the majority of participants in the low category (65%) to high (90%) after the intervention. In addition, 85% of participants were able to demonstrate the RICE/PRICES technique correctly and demonstrated a good understanding of the principles of injury prevention. These findings prove that participatory educational approaches are effective in improving students' preparedness and ability to handle minor sports injuries. These service activities contribute practically to improving sports health literacy in the school environment and theoretically strengthen the application of evidence-based physiotherapy in the context of community health promotion.